Pengaruh Mutasi dan Kepemimpinan Terhadap Kinerja Pegawai dengan Motivasi Kerja Sebagai Variabel Mediasi di Wilayah Kerja Kantor Wilayah DJBC Khusus Papua - Jaryanto, Sidiq; Ginting, Ginta; Nas, Wadzibah (Journal of Authentic Research, 2026)
This study aims to analyze the effect of job rotation (mutation) and leadership on employee performance with work motivation as a mediating variable at the Regional Office of the Directorate General of Customs and Excise (DJBC) Special Papua. This research employs a quantitative approach using a survey method by distributing questionnaires to 158 respondents who are employees of DJBC Special Papua. The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that leadership has a positive and significant effect on employee performance and work motivation. Job rotation (mutation) has a positive and significant effect on work motivation, but does not have a significant effect on employee performance. Furthermore, work motivation has a positive and significant effect on employee performance. In the mediation analysis, work motivation is proven to significantly mediate the effect of leadership on employee performance (partial mediation), but does not mediate the effect of job rotation on employee performance. These findings indicate that leadership is the dominant factor in improving employee performance, both directly and indirectly through work motivation. Meanwhile, job rotation plays a role in enhancing the psychological aspect of employees, particularly work motivation, but has not been able to directly impact performance. Therefore, organizations need to strengthen leadership quality and manage job rotation policies more strategically to support optimal employee performance improvement.